2021
DOI: 10.3390/ijms22157762
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy and COVID-19: The Potential Role of Immune Actors

Abstract: Nowadays, type II diabetes mellitus, more specifically ensuing diabetic nephropathy, and severe COVID-19 disease are known to be closely associated. The exact mechanisms behind this association are less known. An implication for the angiotensin-converting enzyme 2 remains controversial. Some researchers have started looking into other potential actors, such as neuropilin-1, mitochondrial glutathione, vitamin D, and DPP4. In particular, neuropilin-1 seems to play an important role in the underlying mechanism li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Wu et al conducted a study in 49 hospitalized patients on dialysis in Wuhan, China, and found that the disease course was generally more severe in patients with kidney failure than in those without kidney failure [ 18 ]. Hemodialysis patients received more noninvasive ventilation than non-dialysis patients and had a higher rate of complications, including acute respiratory distress syndrome (ARDS), shock, acute cardiac injury, and arrhythmia [ 49 , 50 ]. These findings suggest atypical clinical presentations of COVID-19 in patients on dialysis.…”
Section: Covid-19 and Kidney Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…Wu et al conducted a study in 49 hospitalized patients on dialysis in Wuhan, China, and found that the disease course was generally more severe in patients with kidney failure than in those without kidney failure [ 18 ]. Hemodialysis patients received more noninvasive ventilation than non-dialysis patients and had a higher rate of complications, including acute respiratory distress syndrome (ARDS), shock, acute cardiac injury, and arrhythmia [ 49 , 50 ]. These findings suggest atypical clinical presentations of COVID-19 in patients on dialysis.…”
Section: Covid-19 and Kidney Diseasementioning
confidence: 99%
“…These findings suggest atypical clinical presentations of COVID-19 in patients on dialysis. The symptoms of fatigue and anorexia make the diagnosis difficult, since these symptoms are also observed in uremia, suggesting the need for a more systematic screening approach and universal respiratory precautions [ 49 , 50 , 51 ].…”
Section: Covid-19 and Kidney Diseasementioning
confidence: 99%
See 3 more Smart Citations